CDK4/6 Inhibitors in Hormone Receptor-Positive Metastatic Breast Cancer: Current Practice and Knowledge - de Melo Gagliato, Debora (Cancers (Basel), 2020)
Treatment paradigms in advanced hormone receptor (HR)-positive breast cancer were substantially transformed with cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) approval. The addition of these drugs to endocrine treatment profoundly improved progression-free and overall survival. Additionally, other important endpoints, such as the response rate, time to chemotherapy, and a delay in quality of life deterioration, were positively impacted by CDK4/6 inhibitors’ addition to the treatment of advanced HR-positive breast cancer. This review article will summarize current knowledge on CDK4/6 inhibitors in clinical practice for advanced HR-positive metastatic breast cancer, as well as describe recent efforts to more precisely characterize mechanisms of sensitivity and resistance to these drugs, both on the molecular and clinical characterization level.